Heritage Management. The Natural and Cultural Divide - van Londen, Heleen; Schlaman, Marjo; Marciniak, Arkadiusz (Ex Novo: Journal of Archaeology, 2019)
In 2005, David Lowenthal commented on the dissimilar approaches to natural and cultural heritage and how these differences impact the protection and management of these heritages. His analysis touches on the western European perceptions of nature and culture that go back to the Age of Enlightenment. In his article, the motivation for safeguarding heritage stands out, as nature conservationists emphasize the long-term economic or ecological benefits, while cultural heritage managers point towards cultural or aesthetic benefits (Lowenthal 2005: 87). Others have made similar statements, some eight years later, calling the divide between the domains a fundamental error (Renes 2013; Harrison 2013).